Psychoanalyse des Stinkens. Freuds Erzählung von Genese und Funktion des Ekels (Lebenswelt. Aesthetics and philosophy of experience., 2013)
The evolution of the upright walk is widely considered to be of decisive significance for the evolution of the human being. Freuds gives a highly original reading of this key feature. He emphasizes the distancing of the nose from the organs of sexual secretions and excrement and understands the defensive mechanism of disgust as the organon of turning the archaic pleasures related to the olfactory secretions into unpleasurable sensations. As an antidote to the evolution of morals – which subscribes to the elevation of the nose and pushes the human being in the direction of ‘higher’ values – Freud stresses the inescapability of the abject pleasures and ascribes to art a highly specific capacity to pleasurably address what is otherwise rejected as disgusting.